MINDSET WANITA PENGUSAHA SUKSES - KUSUMADEWI S, RIZKI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Any obstacles in business did not always prevent women entrepreneur to be successful. It was also proven that women played important role in the economic development of the region and the country. This research was conducted to understand the nature of mindset of success among business women. The approach used phenomenology with four respondents. Respondents as successful women entrepreneurs in the field of food, beverages, fashion dan retail, which found by networking. In-depth interview was used to inquire data from the respondents. Data were analyzed with several core processes: epoche, phenomenological reduction, imaginative variation and synthesis of meaning and essences. The credibility of the results of research was obtained using member checking. The results showed that mindset was consist of cognitive component, metacognitive and motivation. Internal structure in the mindset of women entrepreneurs were interdependence, spiritualism, differentiation and learning.